2014
DOI: 10.1007/s10900-014-9836-8
|View full text |Cite
|
Sign up to set email alerts
|

Helmet Use Among Cyclists in New York City

Abstract: Lack of helmet use while bicycling can have deleterious effects on health. Despite evidence that helmets can greatly reduce the risk of head injury, the prevalence of helmet use among riders, including those in urban bicycle-share programs, has been shown to be very low. Building upon the authors' previous work, this study's aim was to assess prevalence of helmet use among cyclists riding on widely used New York City (NYC) bike lanes. Across a 2-month period, cyclists were filmed in five NYC locations with bik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 4 publications
0
19
1
Order By: Relevance
“…Unlike prior research by Basch et al [3], we found no statistical difference in helmet use among gender groups. However, several riding behaviors were dependent on gender, including position on the road, stopping behavior, bicycle type ridden, and light use at night.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike prior research by Basch et al [3], we found no statistical difference in helmet use among gender groups. However, several riding behaviors were dependent on gender, including position on the road, stopping behavior, bicycle type ridden, and light use at night.…”
Section: Discussioncontrasting
confidence: 99%
“…2,3,[14][15][16][17][18][19] An analysis of trauma centre data for bicycle-related injuries for five cities with PBSPs and five comparison cities reported an increase in the proportion of head injuries among bicycle-related injuries in the twelve months following implementation of PBSP. However, aggregate annual injuries were found to decline in bikeshare cities, even as they remained approximately the same in non-share cities.…”
Section: Introductionmentioning
confidence: 99%
“…The 780 survey respondents resided in 32 states. States with 10 or more respondents were Massachusetts (472), Connecticut (79), Illinois (72), New York (29), California (29), Pennsylvania (23), and New Hampshire (10). Demographic data are summarized in Table 1.…”
Section: Demographics and Medical History Of Survey Respondentsmentioning
confidence: 99%